Algorithmic innovations and robust solutions for time windows and stochastic demands in vehicle routing - Desrosiers Goel Zarouk; Chung Wang Xu; Erten Wang Cacchiani (International Enterprise Integration Association, 2022)
This research addresses time windows and stochastic demands in vehicle routing using algorithmic improvements and robust solutions. Optimizing delivery operations requires managing routes and schedules while considering demand uncertainty and severe time frame limits. The research starts with a mathematical formulation that includes consumer locations, stochastic demands, time windows, and costs. Algorithms are added to handle uncertain requests and severe time window restrictions. Demand forecasting, route optimization, and uncertainty-based decision-making are used in the suggested strategy. The proposed routing method models stochastic requests using historical demand data and probability distributions. To create effective delivery plans, it analyzes client visit sequencing, vehicle capabilities, and time window limits. Numerical examples and case studies validate the proposed approach. Numerical examples show how the mathematical theory and algorithm address vehicle routing issues with time windows and stochastic demands. Case studies demonstrate how algorithmic advances and robust solutions benefit logistics firms in real-world circumstances. The proposed approach improves efficiency, cost savings, and customer satisfaction. Optimized routes and timetables help handle uncertain demand patterns, resource use, and time slots. Discussing the solutions' scalability and adaptability sheds light on their application and future research. This research provides algorithmic breakthroughs and robust solutions for vehicle routing time windows and stochastic needs. Logistics companies can increase operational efficiency and customer service with the findings. The proposed method optimizes delivery operations under uncertainty and time restrictions, helping logistics organizations compete in a changing business environment.